1970
DOI: 10.3329/akmmcj.v3i1.10107
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Bacteria Causing Urinary Tract Infections of inpatients and outpatients department at Anwer Khan Modern Medical College Hospital

Abstract: microbial culture of urine. The dip stick method used in many centres serves only as a screening method but culture is needed for final diagnosis 7 . In almost all cases of nosocomial UTI, there is a need to start treatment before the final microbiological results are available. knowledge about the types of pathogens responsible for UTIs and their resistance pattern may help the clinician to choose the correct empirical treatment.Studies from India, Bangladesh and Nepal have reported an increased resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…(4.54%). This study in accordance with many previous studies conducted in Bangladesh those also showed E. coli to be the most prevalent pathogen associated with UTI (Islam and Hasan 2012 ; Khan et al 2013 ; Akter et al 2013 ; Shilpi et al 2012 ; Rahman et al 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…(4.54%). This study in accordance with many previous studies conducted in Bangladesh those also showed E. coli to be the most prevalent pathogen associated with UTI (Islam and Hasan 2012 ; Khan et al 2013 ; Akter et al 2013 ; Shilpi et al 2012 ; Rahman et al 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although water extract was the least active, it exhibited activity of 13.6±0.38 mm against E. coli, 12.6±1.04 mm against B. pumilus and 11.7±1.32 mm against A. calcaoceuticals anitratus. E. coli is by far the most common cause of nosocomial or urinary tract infection among hospitalised patients (Shilpi et al, 2012;Wilson and Gaido, 2004). Moreover, it may produce plasmidmediated AmpC β-lactamases (PABLs) which may be difficult to detect and might interfere with infection control processes (Lee et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This was followed by Proteus spp (22.12%) and Klebsiellaspp(4.05%). Various studies showed Enterococcus fecalis 13 , Klebsiella pnumoniae 14,15 , Staphylococcus aureus 16,17 as second commonest organisms. But this study was contrary to other studies.…”
Section: Discussionmentioning
confidence: 99%